A escola em tempos de festa: poder, cultura e práticas educativas no Estado Novo (1937-1945) - Aline Choucair Vaz (2006)
This work has the objective of analyzing the purpose of the education next to the civic festivities of the Labor's Day and the Patriots Week, in Minas Gerais, in the New State's period (1937-1945). The research objective was to enphatize the value and the increasing of the education, from the civic celebrations, in primary education, for a project of the nation's formation. The meaning of the education, creating children and youngsters, exceeds its own space, and serves of an instrument for the education for the society in general. This research also demonstrates the importance of different ways to attract people to school. The choice for Minas Gerais, was made because of the geographic facilities and better territory boundaries. The choice of primary education - even not being subject of the reform of education in the New State's period - was made by having contemplated effective actions of nationalization of the education, by means of the literacy of the native language, turning into a stage of the high source of the ideas of the strength of the system, in the school and extra-school stuff and also the civic celebrations.